Análisis y diseño de las seguridades sobre sistemas de voip mediante la implementación de session border controller sbc y encriptamiento de paquetes - Paillacho Untuña, Fernando Francisco (2016)
IP telephony is vulnerable to many attacks as they are exposed to various security risks such as unauthorized access and fraud, denial of service attacks on the devices, vulnerabilities of the underlying network, enumeration and discovery level attacks application. For these and other security issues different security methods such as hardware and software are developed to protect information network business is critical, for this reason companies make large investments of resources and efforts to ensure quality of service , but also the integrity and confidentiality of information. Since VoIP networks have disadvantages this project is to design and analysis of VoIP traffic safety by implementing a Session Border Controller (SBC) and encryption of voice packets. Which was used for the SBC BLOX is a free software that allows us to control topology hiding the calls made on the network and also serves as a border or a connection point between a LAN and the Internet. On the other hand, the encryption of voice packets can solve security problems, for which the SRTP protocol which provides integrity and confidentiality, using an authentication algorithm that protects the integrity of the original package with a master key using was used the AES-CM encryption that does not allow the change of master keys.